Generation of high-energy neutrons with the 300-ps-laser system PALS. (1st June 2014) - Krása, J.; Klír, D.; Velyhan, A.; Krouský, E.; Pfeifer, M.; Řezáč, K.; Cikhardt, J.; Turek, K.; Ullschmied, J.; Jungwirth, K.
Abstract: The laser system PALS, as a driver of a broad-beam ion source, delivered deuterons which generated neutrons with energies higher than 14 MeV through the #1#1#1=≤ ==≥ =PrFrRe^7Li(d, n)^8Be reaction. Deuterons with sub-MeV energy were accelerated from the front surface of a massive CD_2 target in the backward direction with respect to the laser beam vector. Simultaneously, neutrons were emitted from the primary CD_2 target and a secondary LiF catcher. The total maximum measured neutron yield from ^2D(d, n)^3He, ^7Li(d, n)^8Be, ^12C(d, n)^13N reactions was 3.5 (± 0.5) × 10^8 neutrons/shot .